ICT in a Global World - Pedro José Arrifano Tadeu; José Maria Fernandez Batanero; Bulent Tarman (Research in Social Sciences and Technology- OpenED Network, 2019)
The impact of everything on society, in general, is increasingly visible, and we find ourselves in a permanent state of transformation and improvement due to the dizzying proliferation of technologies. Information and Communication Technology (ICT) drives the modern world in education, sports, engineering, management, health, tourism, economics, and communication. All have connections, either because ICT is used as a tool or because ICT is the way to solve problems. Starting from these ideas, we decided to create a Special Edition of RESSAT, collecting a wide range of articles and different perspectives regarding the use of ICT around the world. Different areas of knowledge are using and interacting with these new resources, creating a new space for access and production of learning, contributing at the same time to the elimination of barriers so that all people might approach technology in a Global World.